Field calibration of DFM capacitance probes for continuous soil moisture monitoring - Myeni, L; Moeletsi, M.; Clulow, A.D. (Academy of Science of South Africa, 2021)
This study was undertaken to derive textural and lumped site-specific calibration equations for Dirk Friedhelm Mercker (DFM) capacitance probes and evaluate the accuracy levels of the developed calibration equations for continuous soil moisture monitoring in three selected soil types. At each site, 9 probes (3 per plot) were installed in 2 m2 plots, for continuous soil moisture measurements at 5 different depths (viz. 10, 20, 30, 40 and 60 cm) under dry, moist and wet field conditions. Textural site-specific calibration equations were derived by grouping the same soil textural classes of each site regardless of soil depth, while lumped site-specific calibration equations were derived by grouping all datasets from each site, regardless of soil depth and textural classes. Sensor readings were plotted against gravimetrically measured volumetric soil moisture (θv) for different textural classes as a reference. The coefficient of determination (r2) was used to select the best fit of the regression function. The developed calibration equations were evaluated using an independent dataset. The results indicated that all developed textural and lumped site-specific calibration equations were linear functions, withr2 values ranging from 0.96 to 0.99. Relationships between the measured and estimated θv from calibration equations were reasonable at all sites, with r2 values greater than 0.91 and root mean square error (RMSE) values ranging from 0.010 to 0.020 m3∙m-3. The results also indicated that textural site-specific calibration equations (RMSE < 0.018 m3∙m-3) should be given preference over lumped site-specific calibrations (RMSE < 0.020 m3∙m-3) to attain more accurate θv measurements. The findings of this study suggest that once DFM capacitance probes are calibrated per site, they can be reliably used for accurate in-situ soil moisture measurements. The developed calibration equations can be applied with caution in other sites with similar soil types to attained reliable in-situ soil moisture measurements.